Synergizing Artificial Intelligence and HRM for Circular Economy Transition: A Conceptual Framework - Seema Rani; Rubee Singh; A. Arun Kumar (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
The transition to a Circular Economy (CE) has become imperative in addressing globalenvironmental challenges, resource depletion, and achieving long-term sustainability. Thispaper explores the critical synergy between Artificial Intelligence (AI) and Human ResourceManagement (HRM) in accelerating CE adoption. While CE promotes the reuse,regeneration, and recycling of materials to decouple economic growth from resourceconsumption, its successful implementation demands systemic change not only in technologybut also in workforce practices and organizational culture. AI acts as a catalyst by enhancingpredictive analytics, energy efficiency, waste management, and real-time monitoring, therebyoptimizing resource utilization. Simultaneously, HRM plays a transformative role bycultivating green skills, embedding environmental values, and developing leadershipcommitted to circular strategies. This paper is based on secondary sources of data for arrivingat findings and conclusion. This study proposes an integrated AI-HRM based conceptualframework that facilitates personalized training, predictive talent management, and ethicalworkforce governance, thus creating an ecosystem conducive to circular transformation. Byexamining sector-specific applications and emerging economy contexts, the paper highlightshow digital reskilling platforms and AI-driven HR analytics can drive operationalsustainability and employee engagement. The AI-HRM synergy offers a promising pathwayfor embedding CE principles into organizational DNA, aligning technological advancementwith sustainable human capital development. The paper outlines implications for practitioners, policymakers, and researchers, and calls for future empirical and sector-focusedstudies to validate and refine the proposed framework.